2016
DOI: 10.4314/just.v36i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater use in urban agriculture: an exposure and risk assessment in Accra, Ghana

Abstract: In order to minimize the health risks to agricultural workers, and consumers of wastewater irrigated produce, the World Health Organisation has developed guidelines for the safe use of wastewater in agriculture. This study sought to test the appropriateness of the current Quantitative Microbial Risk Assessment model and the multiple-barrier approach advocated by the WHO guidelines.Over a one year period, over 500 produce and ready-to-eat salad samples were collected from fields, markets, and kitchens in Accra,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…and staphylococci contamination [65]. In another study, Escherichia coli O157: H7 was found in over 80% of the product, but the topmost contamination was observed in street food salads (4.23 log10 cfu/g) [66]. Salads from a University campus in Bangladesh were also contaminated with Escherichia coli O157: H7, Salmonella spp., and Staphylococcus spp.…”
Section: Vegetable Salads From Restaurants and Canteensmentioning
confidence: 94%
See 1 more Smart Citation
“…and staphylococci contamination [65]. In another study, Escherichia coli O157: H7 was found in over 80% of the product, but the topmost contamination was observed in street food salads (4.23 log10 cfu/g) [66]. Salads from a University campus in Bangladesh were also contaminated with Escherichia coli O157: H7, Salmonella spp., and Staphylococcus spp.…”
Section: Vegetable Salads From Restaurants and Canteensmentioning
confidence: 94%
“…However, it has also been pointed out that though irrigation water is more contaminated, the soil remained a major route for contamination. is is a result of the direct access farmers have to soil such that some (93%) worked barefooted, while others (86%) have direct hand contact with contaminated soil, which leads to oral contamination during hand-to-mouth events [66].…”
Section: Major Sources Of Contaminationmentioning
confidence: 99%
“…The hazard from consumption of urban vegetable products in countries with a low level of industrial development is mainly related to bacteriological environmental pollution. Agyei and Ensink [ 24 ] studied 500 samples of salad from Accra, Ghana. The excess of the content of intestinal bacteria was found above 80% in the chosen samples.…”
Section: Introductionmentioning
confidence: 99%